2017
DOI: 10.1155/2017/8747013
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Backscatters as an Objective Index for Assessing Fuchs’ Endothelial Corneal Dystrophy: A Pilot Study

Abstract: Purpose To provide an objective, quantitative approach for monitoring Fuchs' endothelial corneal dystrophy (FECD), with Scheimpflug imaging. Design This is a retrospective case-control pilot study. Methods The study group consisted of 53 eyes in 27 patients diagnosed with FECD, with normal subjects paired as control. Main outcome measures were corneal thickness, morphological patterns on densitograms, and indices of corneal density including the average area density (mean AD) and the average ratio of Descemet'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…We strongly believe that the presence of abnormal accumulation of macromolecules with irregularities in corneal water content and collagen fiber diameter may influence the light scattering of OCT signal trough the cornea, thus leading to the pattern 2 or 3. A similar mechanism has already been described by Chu et al in 2017 [22]. Indeed, the authors analyzed the backscattered light from the corneal tissue by a Pentacam Scheimpflug densitometry, stating that both abnormalities in corneal thickness and composition may contribute to change its optical properties in FECD patients.…”
Section: Discussionsupporting
confidence: 62%
“…We strongly believe that the presence of abnormal accumulation of macromolecules with irregularities in corneal water content and collagen fiber diameter may influence the light scattering of OCT signal trough the cornea, thus leading to the pattern 2 or 3. A similar mechanism has already been described by Chu et al in 2017 [22]. Indeed, the authors analyzed the backscattered light from the corneal tissue by a Pentacam Scheimpflug densitometry, stating that both abnormalities in corneal thickness and composition may contribute to change its optical properties in FECD patients.…”
Section: Discussionsupporting
confidence: 62%
“…Although various factors affecting visual acuity, such as high-order aberrations, subjective forward light scattering, and corneal backscatter, have been investigated in eyes with Fuchs' endothelial corneal dystrophy, which factor is the most effective in vision expectancy after surgery remains a controversial issue. [9][10][11]30 In eyes with subclinical corneal edema, there was a positive correlation between the 6-mm trefoil measurement and best-corrected visual acuity. In our study, more patients in the Fuchs' endothelial corneal dystrophy-edema group with intermediate values (between a large set of data points and a few "outliers") are required to assess the correlation of other aberrations with best-corrected visual acuity.…”
Section: Discussionmentioning
confidence: 93%
“…Clinical evaluation of the back-scattered light or, in other words, optical corneal densitometry plays an important role in the evaluation of the corneal status and progression of some ocular diseases, such as keratoconus. 17 18 19 20 As mentioned earlier, optical corneal densitometry is the outcome of the order of collagen fibers, extracellular matrix, and keratocyte harmony; 19 21 therefore, it can be expected that the placement of an intracorneal ring would alter the balance of the above-mentioned factors and eventually change the optical corneal densitometry. In a study on 18 rabbits, Salamatrad et al ., observed that the keratocyte cell density was not different between the control and inlay-treated groups that had an AICI ring placed into their corneas.…”
Section: Discussionmentioning
confidence: 95%